White Spot Syndrome Virus (WSSV) Detection at Traditional Ponds of Lithopenaeus vannamei in Pasuruan District - Usman, Ali; Andayani, Sri; Herawati, Endang Yuli (Graduate School, Universitas Brawijaya, 2018)
Vanamei shrimp (Litopenaeus vannamei) is a type of shrimp that widely cultured in Indonesia. Pasuruan is one of the districts where there are many ponds that culture shrimp Vaname (L. vannamei) traditionally. The occurrence of a decrease in production due to WSSV virus attacks that cause a lot of losses for farmers so it needs a preventive effort by doing early warning and monitoring on the existence of the virus. The study was conducted from April to May 2018 with the aim of obtaining data on the presence of WSSV virus and its prevalence at traditional Vaname shrimp farms (L. vannamei) in Pasuruan District. The sampling location is located in Pasuruan District consisting of three locations namely Bangil, Kraton, and Rejoso with each has 10 ponds (total of 30 ponds site). Detection of White Spot Syndrome Virus using Nested PCR with shrimp section taken is swimming foot, road leg, and tail. PCR results in 848 bp and 333 bp indicated the presence of WSSV infection in the Bangil and Rejoso ponds where the prevalence rate of WSSV attack in each region differs from Bangil 0 - 15%, Kraton 0% and Rejoso 0 - 15%.Keywords: PCR, Prevalence, Shrimp, Vannamei, WSSV.